Pengaruh Sistem Pengukuran Kinerja, Motivasi, dan Kompensasi terhadap Kinerja Karyawan - Dian Ayu Sartika (Jurnal Ekonomi Akuntansi dan Manajemen, 2017)
The aims of this research is to know the effect of performance measurement system, motivation, and compensation on employees performance. The data collection of this research is done by spreading questionair to the 70 employees in PTPN XII region Kendeng Lembu Glenmore. The research method of this research multiple linier regression analysis, classical analysis assumption and hypothesis test (t-test). The measurement scale of this research is likert scale and the scale is 1 up to 5 starting with very less appropriate statement. The result of linier regression analysis show that performance measurement system, motivation, compensation have significan impact to the employees performance. Keywords: performance, system performance, motivation, compensation, employees performance